DETERMINAN PERSEPSI MENGENAI ETIKA ATAS PENGGELAPAN PAJAK (TAX EVASION) - Mujiyati, Mujiyati; Rohmawati, Fitria Riski; Ririn, Wahyu Hening (Universitas Muhammadiyah Surakarta, 2018)
AbstractThis study aims to examine the factors that influence the perception of ethics on tax evasion in the lecturers and students of Muhammadiyah University of Surakarta. The variables used in this study are the dependent variables, namely the perception of ethics on tax evasion, while the independent variables used Are justice, taxation systems, discrimination, the quality of tax services, and the possibility of fraud detection.The sample in this research is lecturer and student at university muhammadiyah surakarta. Sample collection method used in this research is convenience sampling taken 84 sample lecturer and 100 student sample. The data used in this study is the primary data by using questionnaires. Data analysis in this research is assisted by using SPSS program. Data analysis technique used is multiple linear regression.The result of the research shows that significant at level 0,05 variable of system of taxation to lecturer, discrimination on lecturer and student, and quality of tax service to lecturer and student have significant influence to perception about ethics on tax evasion. While the variable of justice in lecturer and student, system of taxation to student, and possibility of detection of fraud on lecturer and student have no effect and insignificant to perception about ethics of tax evasion.Â Keywords: ethical perception, tax evasion, justice taxation system, discrimination, quality of tax service, possible fraud detection.